PENGGUNAAN BERBAGAI ARTIFICIAL INTELLIGENCE PADA PROSES AUDIT- A SYSTEMATIC LITERATURE REVIEW - Silaen, Raymonth Pieter; Dewayanto, Totok (Diponegoro Journal of Accounting, 2024)
This research aims to determine the importance of using various artificial intelligence in the audit process. The method used in this research is Systematic Literature Review (SLR) by searching for articles in the Scopus database. The research results show that the application of AI in the audit process can increase audit efficiency and effectiveness. Apart from that, AI also helps auditors with data analysis and fraud detection. However, there are several obstacles to using AI in audits, such as the auditor's lack of understanding of AI technology. This research is expected to contribute to the development of science and technology, especially in the audit field. In addition, the results of this research are expected to provide benefits for auditors in carrying out the audit process. In this research, the author found 20 articles that were relevant to the research topic. This research concludes by discussing the implications of the research for the future of auditing. The findings show that AI has the potential to significantly improve the efficiency, accuracy, and effectiveness of the audit process. However, there are challenges that need to be overcome, such as the need for auditors to develop new skills and regulatory adaptation to the use of AI in audits.